System Informasi Surat Menyurat Kelurahan Sambirejo Berbasis Web - Izzatul Umami; Ryan Wijaya; Gugus Gugus (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Sambirejo Village is one of the Villages in Jogoroto District, Jombang Regency, Sambirejo Village is a village in Jogoroto District, Jombang, East Java. Which has an area of ​​1,115.09 km2. Sambirejo village has a population of 5,628 people, consisting of 2,975 men and 2,653 women. Advances in the field of Information Technology have recently grown very rapidly, one of which is marked by the presence of computers, computers which were initially only used by academics and the military have now been widely used, with computers people can access the internet. Through the Internet, people can exchange information without having to meet face-to-face so that it is easier and faster to use. Besides that, the use of computers can be applied in various fields and all circles as well as information obtained starting from Data Access, Actual Information, Advertising, Communication, and so on. This technological advancement requires government agencies to follow technological developments and continue to improve their capabilities in managing data and information as well as creating convenience, timeliness of work in managing information data. Likewise, a government agency requires an information system. Therefore, my goal is to create a Web-based Village Service to make it easier for applicants or the community in population administration services.